2018
DOI: 10.1152/japplphysiol.00869.2017
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for direct effects of recombinant human erythropoietin on cerebral blood flow and metabolism in healthy humans

Abstract: Erythropoietin (EPO) is expressed in human brain tissue, but its exact role is unknown. EPO may improve the efficiency of oxidative metabolism and has neuroprotective properties against hypoxic injuries in animal models. We aimed to investigate the effect of recombinant human EPO (rHuEPO) administration on healthy cerebral metabolism in humans during normoxia and during metabolic stress by inhalation of 10% O hypoxic air. Twenty-four healthy men participated in a two-arm double-blind placebo-controlled trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Data reported in this study were obtained from healthy control subjects in multiple studies on the effect of inhalation of hypoxic air as follows: patients with obstructive sleep apnea (study A), 23 patients with migraine (study B), 24,25 healthy subjects treated with erythropoietin (study C), 17,26 freedivers (study D), 16 and a pilot study on healthy subjects (study E). By combining data from multiple studies, we obtained sufficient power of the statistics to examine the subtle effects from normal aging.…”
Section: Methodsmentioning
confidence: 99%
“…Data reported in this study were obtained from healthy control subjects in multiple studies on the effect of inhalation of hypoxic air as follows: patients with obstructive sleep apnea (study A), 23 patients with migraine (study B), 24,25 healthy subjects treated with erythropoietin (study C), 17,26 freedivers (study D), 16 and a pilot study on healthy subjects (study E). By combining data from multiple studies, we obtained sufficient power of the statistics to examine the subtle effects from normal aging.…”
Section: Methodsmentioning
confidence: 99%
“…Haemoglobin was set to 9 mmol/l for all subjects, and arterial oxygen saturation was set to 98% for all subjects, since previous studies have shown that these do not differ significantly between MS and healthy controls. 32 We measured SvO 2 in the superior sagittal sinus using a susceptibility-based oximetry (SBO) MRI technique. 33 This technique utilises venous blood, which has a different magnetic susceptibility than brain tissue, and this difference is related to oxygen saturation.…”
Section: Mrimentioning
confidence: 99%
“…Recombinant human erythropoietin (rhEPO) is a drug commonly used for the treatment of renal insufficiencyinduced anemia in clinical practice. A pharmacological study proved that rhEPO can resist oxidation and apoptosis and promote nerve cell regeneration [6] . A recent study proved that rhEPO was able to protect brain tissues in TBI and had great potential in treating neurological diseases including stroke, cerebral hemorrhage and TBI [7] .…”
mentioning
confidence: 99%